Comparative Assessment of the Incidence of Unilateral and Bilateral Lower Limb Deep Venous Thrombosis in Symptomatic and Clinically Suspected Patients - Wazzan, Mohammad; Abduljabbar, Ahmed; Batawil, Nadia; Alharthy, Ahmed; Elkhadir, Awad; Alzahrani, Yehya; Rani Ahmed (Journal of Contemporary Medical Sciences, 2024)
Objective: Deep vein thrombosis (DVT) is a familiar coagulation pathology that can be diagnosed through Doppler ultrasonography. This is a highly specific and sensitive method for the assessment of thrombosis. The present study aims to assess the incidence of lower limb DVT in a cohort of symptomatic and clinically suspected Saudi Arabian patients. Methods: This is a retrospective study that incorporated 1051 DVT patients over three years between January 2015 and December 2017 which presented with signs and symptoms of single or bilateral disease. Data were collected on the history of oedema, swelling, pain, tenderness, weakness, hotness, redness, fever, and vomiting. Possible risk factors that may increase the probability of developing DVT were also recorded. Results: The incidence of bilateral lower limb DVT in suspected patients was 84.5% negative and 15.5% positive. Old age was found to be the most common risk factor that resulted in DVT. The incidence of DVT is more common among females, whereas males were with all the bilateral cases. Conclusions: Screening tests are needed for DVT in symptomatic and asymptomatic patients.